Preliminary analyses on technical and economic viability of moon-mined propellant for on-orbit refueling. (March 2023) - Sommariva, Andrea; Gaudenzi, Paolo; Pianorsi, Mattia; Pasquali, Michele; Vittori, Edoardo; Eugeni, Marco; Italiano, Matilde; Telli, Chiara; Di Nicola, Miriam; Gori, Leonella; Chizzolini, Barbara
Abstract: The present study analyses the technical feasibility and economic sustainability of Moon-mined propellant transportation, storage, and distribution to final users. Two technical architectural options are considered for propellant transportation: taking fuel from the Moon or from Earth. Both architectures assume the same storage and distribution system, i.e., the use of an orbiting depot. The depot will be reachable by various types of spacecrafts for refueling. Both architectures are evaluated in terms of technical feasibility, performance and economic convenience. As the estimates of the investment, operational costs, and revenues are highly uncertain, a risk evaluation, i.e. the Monte Carlo analysis, is used to evaluate the exposure of the ventures to factors that could affect the volatility of results and lead them to fail. These analyses identify transporting propellant from the Moon as the most promising solution. Highlights: Lunar-based propellant storage and distribution through a EML 1 depot is technically feasible and economically convenient. Montecarlo simulations indicate lower riskiness for a lunar-based propellant infrastructure compared to Earth options. The presence of a competitive space could incentivize institutional and private investors.